Organizational Performance Determination: Analysis of Organizational Culture, Leadership Style, Information Technology and Competence - Liana, Esti; Triyuwono, Iwan (Siber International Journal of Digital Business (SIJDB), 2025)
The purpose of this literature study is to develop a hypothesis regarding the influence between variables that can later be used for further research in the field of human resource management. The literature review research article on determining organizational performance: analysis of organizational culture, leadership style, information technology and competence is a scientific literature article in the field of human resource management. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use a literature study or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research relevant to this research and is sourced from academic online media such as Thomson Reuters, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. The results of this literature review article are: 1) Organizational Culture affects Organizational Performance; 2) Leadership Style affects Organizational Performance; 3) Information Technology affects Organizational Performance; and 4) Competence affects Organizational Performance.